Citrus transcription factor CsHB5 regulates abscisic acid biosynthetic genes and promotes senescence. (19th August 2021) - Zhang, Yin; Zhang, Yingzi; Sun, Quan; Lu, Suwen; Chai, Lijun; Ye, Junli; Deng, Xiuxin
SUMMARY: Senescence is a gradual physiological process involving the integration of numerous internal and environmental signals. Abscisic acid (ABA) is a well‐known inducer of senescence. However, the regulatory mechanisms underlying ABA‐mediated senescence remain largely unknown. Here, we report that the citrus homeodomain leucine zipper I (HD‐ZIP I) transcription factor CsHB5 functions as a regulator of ABA‐triggered senescence. CsHB5 acts as a nucleus‐localized transcriptional activator, the expression of which appeared to be closely associated with citrus senescence. Overexpression of CsHB5 in citrus calli upregulated the expression of ABA‐ and reactive oxygen species (ROS)‐related genes, and significantly increased the content of ABA and hydrogen peroxide (H2 O2 ), whereas silencing CsHB5 in citrus calli downregulated the expression of ABA‐related genes. Additionally, heterogenous overexpression of CsHB5 in Solanum lycopersicum (tomato) and Arabidopsis thaliana (Arabidopsis) leads to early leaf yellowing under dark‐induced senescence conditions. Meanwhile, the levels of ABA and H2 O2 in transgenic tomatoes increased significantly and the lycopene content decreased. Transcriptome analysis of CsHB5 ‐overexpressing citrus calli and tomato showed that CsHB5 was involved in multiple senescence‐associated processes, including chlorophyll degradation, nutrient compound biosynthesis and transport, as well as ABA and ROS signal transduction. The results of yeast one‐hybrid assays, electrophoretic mobility shift assays and dual luciferase assays indicated that CsHB5 directly binds to the promoters of ABA biosynthetic genes, including β‐carotene hydroxylase 1 ( BCH1 ) and 9‐ cis ‐epoxycarotenoid dioxygenase 2 ( NCED2 ), thereby activating their transcription. Our findings revealed that CsHB5 participates in senescence, at least partly, by directly controlling ABA accumulation. Our work provides insight into the regulatory mechanisms underlying ABA‐mediated senescence. Significance Statement: Abscisic acid (ABA) is a well‐defined inducer of senescence. However, the regulatory mechanisms underlying ABA‐mediated senescence remain largely unknown. Here we report that transcription factor CsHB5 directly binds to the promoters of ABA biosynthetic genes and activates their expression to promote ABA accumulation, thereby triggering senescence. This study provides insight into the regulatory mechanism underlying ABA‐mediated senescence.